GEOCHEMISTRY AND PETROGENESIS OF VOLCANIC ROCKS AND THEIR MANTLE SOURCE IN THE EAST VIETNAM SEA AND ADJACENT REGIONS IN THE CENOZOIC - Anh, Le Duc; Hoang, Nguyen; Phach, Phung Van; I., Malinovskii A.; A., Kasatkin S.; V., Golozubov V. (Vietnam Journal of Marine Science and Technology, 2018)
The East Vietnam Sea is one of the largest marginal basins in western Pacific Ocenan, formed by breaking of continental margin in the Late Mesozoic. Geochemical data of the Miocene - Pleistocene bazanic samples collected in the East Sea and neighboring areas show two major eruption trends that reflect the formation and development of the region. The early eruption event is characterized by low alkaline, TiO2, Na2O, K2O and P2O5, and high SiO2 group, comprising olivine and tholeiitic bazans. The later eruption demonstrates high alkaline, TiO2, Na2O, K2O and P2O5, and low SiO2 group, mainly generated by central-type volcanic eruptions, consisting of alkaline olivine and olivine bazans. Distinctive geochemistry of the volcanic rocks within the East Vietnam Sea and adjacent areas is illustrated by wide range of Magnesium index (Mg#= 35-75). At the values of Mg#>65, the relation between Mg# and major oxides is unclear. In contrast, Mg#65 (Olivine differentiation) the isotope ratios start changing. The primitive components are computed based on the principle of olivine compensation. The computed results show that the critical pressure for Tholeiite melting was estimated from ~11.97-20.33 Kb (ca. 30 - 60 km deep) and the Alkaline melting pressure varies from ~16.87-34.93 Kb (corresponding to the depths of ~60 km to 100 km). The continuous range of melting pressures suggests two trends of tholeiitic and alkaline eruptions occurr at various depths in the same magmatic source. Hight temperature and melting pressure of the primitive magma are dependent on partial melting pressure. Possibly, this process was triggered by the asthenosphere intrusion resulted from the closure of the Neo-Tethys following the India - Eurasia collision. This event has not only made the mantle hotter and easily melted but also triggered the opening of the marginal seas, including the East Vietnam Sea.